Henry V the astonishing triumph of England's greatest warrior king - Jones, Dan 1981- (Viking, 2024)
"The New York Times bestselling author returns with a biography examining the dramatic life and unparalleled leadership of England's greatest medieval king. In 1413, when Henry V ascended to the English throne, his kingdom was hopelessly torn apart by political faction and partisanship. Public finances and law and order were in a state of crisis. Pirates tormented the coast; plots, conspiracies, and heresy threatened society. The lingering effects of the worst pandemic in human history continued to menace daily life. And then, in less than ten years, Henry turns it all around. By common consensus in his day, and for hundreds of years afterward, Henry was the greatest medieval king that ever lived. Through skillful leadership, unwavering vision, and seemingly by sheer force of personality, he managed to catapult his realm into the greatest triumphs it has ever achieved: he united the political community behind the crown, renewed the justice system, revived England's maritime dominance. And then there are his military achievements in France, most notably the resounding, against-the-odds victory at Agincourt. He was tough, lucky, intelligent, farsighted, and cultured. But he was also, at times, cold, callous, violent, by instinct a traditionalist and even a reactionary. A historical titan, his legacy over the years has become a complicated one. As an exceptional leader, Henry V transcends the Middle Ages which produced him, and his life story has much to teach us today. Drawing on the latest scholarship and writing with his characteristic wit and style, Dan Jones examines the king's legendary life-and he puts Henry's claim to greatness very vigorously to the test."
Keywords: Heinrich -- V. -- England, König -- 1387-1422; Henry / V / King of England / 1387-1422; Great Britain / History / Henry V, 1413-1422; Great Britain / Politics and government / 1399-1485; Great Britain / Kings and rulers / Biography; Grande-Bretagne / Histoire / 1413-1422 (Henri V); Grande-Bretagne / Politique et gouvernement / 1399-1485; Informational works; Biographies; Documents d'information; Biografie